Crédito rural e as fintechs no agronegócio - Tófoli, Ana Clara (Universidade Federal de São Carlos, 2022)
Rural credit is an instrument of great importance for agricultural policy and for the rural producer, however, many producers still find it difficult to access credit. With the increased use of technologies in the field, the way of offering rural credit to the producer has been modernized. In this way, the general objective of the work is to describe the role of fintechs and their performance in Brazilian agribusiness through the granting of rural credit to producers. Using exploratory research, it was possible to verify that the role of fintechs becomes relevant, considering that they mainly serve small and medium-sized producers, providing financing in a simpler, faster and more democratic way.
Rural credit and fintechs in agribusiness
Keywords: Startup; Produtor Rural; Concessão de crédito; Rural producer; Granting credit; CIENCIAS SOCIAIS APLICADAS::ECONOMIA